"New classification of late and delayed complications after dermal filler: Localized or Generalized?". (16th November 2020) - Ryu, Hwa Jung; Kim, Bo Young; Ryu, Sook In; Kim, Na Young; Ko, Joo Yeon; Ro, Young Suck; Kim, Il-Hwan; Kim, Jeong Eun
ABSTRACT: Background: As filler injections have become very common procedures worldwide, the number of complications has increased. However, there is a lack of systematized studies and precise classification of late and delayed complications. This study aimed to suggest new and reliable classifications and to characterize the clinical manifestations of late and delayed complications after filler injections.Methods: This retrospective study analyzed patients and suggested a new classification of delayed adverse effects related to filler injection. Several demographic and clinical findings were analyzed. Patients were classified into two types according to their clinical presentation: Type I (Localized) or Type II (Generalized).Results: Twenty-five patients were evaluated during a clinically active adverse event suspected to be related to fillers. The most common injected filler substance was hyaluronic acid (HA, 68.8%). 76% of the patients were classified with Localized complications. In the Generalized complications group, systemic symptoms were more common (p=0.002), the treatment response was poor (p=0.010), and fewer patients showed complete remission (p=0.007) than in the Localized complications group.Conclusions: We propose a simple new classification method for late and delayed complications after dermal filler: Localized and Generalized. We expect that this new classification could help provide appropriate treatment and predict patient prognosis.